2017
DOI: 10.1111/mec.13961
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Escherichia coli type I‐E CRISPR spacers over 42 000 years

Abstract: CRISPR-Cas are nucleic acid-based prokaryotic immune systems. CRISPR arrays accumulate spacers from foreign DNA and provide resistance to mobile genetic elements containing identical or similar sequences. Thus, the set of spacers present in a given bacterium can be regarded as a record of encounters of its ancestors with genetic invaders. Such records should be specific for different lineages and change with time, as earlier acquired spacers get obsolete and are lost. Here, we studied type I-E CRISPR spacers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…These gene family expansions are often located in the recombinogenic parts of the genome, which could also apply to the phage genomes in our dataset, as the additional ORFs are found upstream of ORF66, which contains a putative ICE (Integrative and The presence of CRISPR/Cas systems has been found in approximately 40% of studied bacterial species 32 , and the molecular mechanisms of different CRISPR systems are under rigorous research 40 . Some repeat-spacer arrays remain relatively constant over millennia 41 , while in some cases no two identical CRISPR loci are found in cells living in close proximity 22 . A study on a closely related species, the fish pathogen Flavobacterium psychrophilum, identified only inactive CRISPR loci across multiple strains 42 .…”
Section: Discussionmentioning
confidence: 99%
“…These gene family expansions are often located in the recombinogenic parts of the genome, which could also apply to the phage genomes in our dataset, as the additional ORFs are found upstream of ORF66, which contains a putative ICE (Integrative and The presence of CRISPR/Cas systems has been found in approximately 40% of studied bacterial species 32 , and the molecular mechanisms of different CRISPR systems are under rigorous research 40 . Some repeat-spacer arrays remain relatively constant over millennia 41 , while in some cases no two identical CRISPR loci are found in cells living in close proximity 22 . A study on a closely related species, the fish pathogen Flavobacterium psychrophilum, identified only inactive CRISPR loci across multiple strains 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a comparative analysis of E. coli CRISPR spacers recovered from intestines of a 42 000‐year‐old mammoth with present‐day E. coli did not support intensive change through adaptive acquisition over time (Savitskaya et al . ).…”
Section: Insights On Microbial Adaptation From Patterns Of Local Adapmentioning
confidence: 97%
“…2). Furthermore, in Escherichia coli, the only microbe for which the virome can be considered comprehensively characterized, there are virtually no spacers with matches to the known viral genomes, suggesting that the apparently inactive CRISPR arrays in this bacterium have accumulated mismatches to the cognate protospacers that render them unrecognizable (75). Further characterization of the pan-mobilomes of diverse bacteria and measurement of spacer amelioration rates should improve our understanding of the evolution of the CRISPR spacer space and the virus-host arms race.…”
Section: Discussionmentioning
confidence: 99%